2004
DOI: 10.1081/mb-200033278
|View full text |Cite
|
Sign up to set email alerts
|

Microhardness Studies of the Interphase Boundary in Rubber‐Softened Glassy Polymer Blends Prepared with/without Compatibilizer

Abstract: The interphase boundary of incompatible polymer blends such as poly(methyl methacrylate) (PMMA)/natural rubber (NR) and polystyrene (PS)/NR, and of compatible blends such as PMMA/NR/epoxidized NR (ENR) and PS/NR/styrene -butadienestyrene (SBS) block copolymer, where ENR and SBS were used as compatibilizers, was studied by means of microindentation hardness (H) and microscopy. Cast films of neat PMMA and PS, and blended films of PMMA/NR, PS/NR, PMMA/NR/ ENR, and PS/NR/SBS were prepared by the solution method us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…Figure a,b displayed Young’s modulus ( E ) and microhardness ( H ) of the composites by nanoindentation technique which is a widely used method to the characterize the mechanical behavior of materials at small scales . The results (Figure ) showed that E and H of neat PS were 0.14 and 4.32 GPa, respectively, which were roughly consistent with the reported value 0.17 GPa , and 2–5 GPa . The values significantly increased with the loading of fillers.…”
Section: Resultssupporting
confidence: 80%
“…Figure a,b displayed Young’s modulus ( E ) and microhardness ( H ) of the composites by nanoindentation technique which is a widely used method to the characterize the mechanical behavior of materials at small scales . The results (Figure ) showed that E and H of neat PS were 0.14 and 4.32 GPa, respectively, which were roughly consistent with the reported value 0.17 GPa , and 2–5 GPa . The values significantly increased with the loading of fillers.…”
Section: Resultssupporting
confidence: 80%
“…The structural and morphological features obtained for un-irradiated specimens of semi-IPNs using Fourier Transform Infrared Spectroscopy (FTIR), Environmental Scanning Electron Microscopy (ESEM) and X Ray Diffraction (XRD) helps in understanding the overall effect of irradiation on the microhardness. The Vickers microhardness testing method is found to be versatile in revealing the structural, morphological and plasticization aspects in polymers [27].…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, it has been shown that the microhardness values of uncompatibilized PP/liquid crystalline polymer blends are close to the additive ones, while for compatibilized blends, a strong positive deviation from additivity has been established [39]. Concerning the glassy polymer blends, it has been demonstrated that after the inclusion of soft styrene–butadiene–styrene block copolymer in PS/natural rubber blends, the microhardness values markedly decrease [40]. The changes of the microhardness of poly (methyl methacrylate)/natural rubber blends are correlated with the variation of the glass transition temperature [41].…”
Section: Introductionmentioning
confidence: 99%